GAMBARAN TINGKAT STRESS KERJA ANTAR SHIFT KERJA PADA PETUGAS PENGUMPUL TOL SURABAYA - Zahra, Ayyuda Asyraf (Universitas Airlangga, 2015)
ABSTRACTPT. (X), Surabaya is one of company that manages toll road or highway that implement the shift system of work. Shift work has the potential for job stress and other health problems. The purpose of this research was to identify descriptive the level of job stress between shift work at the toll collector in PT. (X), Surabaya. This research was an observational analytic study with cross sectional approach. 36 toll collector who work when the morning shift, afternoon, and evening at the toll gate x, toll gate y and toll gate z were chosen as sample by using Proportional Random Sampling method. The results showed when the shift I (morning) there were 15 respondents (41.7%) suffered mild job stress and 21 respondents (58.3%) suffered moderate job stress. At the shift II (evening) there were 12 respondents (33.3%) suffered mild stress of work and 24 respondents (66.7%) suffered moderate job stress, while at the shift III (evening) were 9 respondents (25%) suffered light work stress and 27 respondents (75%) suffered moderate job stress. Based on the research results, it can be concluded the level of job stress between of shift work on the toll collectors suffered mild and moderate stress. The greatest frequency of respondents suffered moderate job stress. Recommendation for the company is review the system of career development and maintaining training activities, while for workers is use the time to rest and regular exercise.Keywords: job stress, shift work, toll collector